Question
upstudy study bank question image url

Simplify: \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) Hence: 2.2.1 Determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \), if \( x=-3 \) 2.2.2 solve for \( x \) if: \[ \frac{x^{4}+x}{x^{3}-x^{2}+x}=2 \]

Ask by Klein Newton. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified form of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) is \( x+1 \). When \( x = -3 \), the expression equals \( -2 \). When \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \), \( x = 1 \).

Solution

Calculate or simplify the expression \( (x^4+x)/(x^3-x^2+x) \). Simplify the expression by following steps: - step0: Solution: \(\frac{\left(x^{4}+x\right)}{\left(x^{3}-x^{2}+x\right)}\) - step1: Remove the parentheses: \(\frac{x^{4}+x}{x^{3}-x^{2}+x}\) - step2: Factor the expression: \(\frac{\left(x^{3}-x^{2}+x\right)\left(x+1\right)}{x^{3}-x^{2}+x}\) - step3: Reduce the fraction: \(x+1\) The simplified form of the expression \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) is \( x+1 \). Now, let's determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) when \( x = -3 \). Substitute \( x = -3 \) into the expression \( x+1 \): \[ \frac{(-3)^{4}+(-3)}{(-3)^{3}-(-3)^{2}+(-3)} = \frac{81-3}{-27-9-3} = \frac{78}{-39} = -2 \] Therefore, when \( x = -3 \), the value of the expression is \( -2 \). Next, let's solve for \( x \) when \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \). Set the expression equal to 2: \[ x+1 = 2 \] Solving for \( x \): \[ x = 2 - 1 = 1 \] Therefore, when \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \), the value of \( x \) is 1.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To simplify the expression \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \), we start by factoring both the numerator and the denominator. In the numerator: \[ x^{4} + x = x(x^{3} + 1) = x(x + 1)(x^{2}-x+1) \] In the denominator: \[ x^{3} - x^{2} + x = x(x^{2} - x + 1) \] Now we can rewrite the expression: \[ \frac{x(x + 1)(x^{2}-x+1)}{x(x^{2}-x+1)} \] Assuming \( x \neq 0 \) and \( x^{2}-x+1 \neq 0 \), we can cancel \( x \) and \( (x^{2}-x+1) \): \[ \frac{x + 1}{1} = x + 1 \] Now, let's solve the subproblems: ### 2.2.1 To determine the value of \( \frac{x^{4}+x}{x^{3}-x^{2}+x} \) at \( x = -3 \): Substituting \( x = -3 \) into the simplified expression \( x + 1 \): \[ -3 + 1 = -2 \] So, \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = -2 \) when \( x = -3 \). ### 2.2.2 To solve for \( x \) in the equation \( \frac{x^{4}+x}{x^{3}-x^{2}+x}=2 \): Using the simplified version \( x + 1 = 2 \): \[ x + 1 = 2 \] Subtracting 1 from both sides gives: \[ x = 1 \] Thus, the solutions are: \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = -2 \) at \( x = -3 \), and \( x = 1 \) satisfies the equation \( \frac{x^{4}+x}{x^{3}-x^{2}+x} = 2 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy